A Life in Costume: How the Journal Recorded the Costume Society. (June 2015) - Kim, Alexandra
<x content-type="archive" xml:space="preserve">Abstract</x> To celebrate fifty years of the Costume Society and the free online access which Costume's publishers' Maney are providing to Society members, this article explores a variety of features in the journal which highlight the history of the Society and the way in which it has played a pivotal role in advancing the study of dress history. In particular the article considers personal recollections, obituaries, and notes and queries and the wealth of information to be found within them.